Estimating the Tax Advantage of Corporate Debt - CORDES, JOSEPH J.; SHEFFRIN, STEVEN M. (Journal of Finance, 1983)
ABSTRACT This paper presents estimates of the effective tax value of incremental interest deductions for corporations taking into account that they may not be able to utilize all their interest deductions fully because of either insufficient taxable income or the availability of nondebt tax shields. After describing particular features of the tax code which may drive a wedge between statutory and effective tax rates for debt finance, we present estimates using the Treasury Corporate Tax Model of effective tax rates for a variety of industry groupings. Our estimates suggest that the after‐tax cost of debt varies widely across industries.